Congenital scaphoid megalourethra - Kouame Soroboua Agbara; Martial Olivier Mama Moulot; Ehua Adjoba Manuela; Jean-Marie Konan; Ibrahim Traore; Landry Konan; Ghyslain Anon Anon; Idalia Ajoumissi; Leopold Assogba Azakpa; Josaphat Konvolbo; Roumanatou Sanni Bankole (Elsevier, 2018)
The congenital megalo-urethra is a rare malformation of the urogenital tract characterized by the dilation of the anterior urethra due to an absence of erectile tissue within the penis. The objective of present paper is to report the management of 02 cases and performed a literature review. 5-day-old and 5-months boys were admitted in our institution for a scaphoid penile dilation. The physical examination and the urethroscopy confirmed the diagnosis. No associated malformations were found. The patients underwent successful urethroplasty and no adverse outcomes were encountered at 1 year and 3 years post-operative respectively. The congenital scaphoid megalo-urethra is curable surgically; however, the pronostic is dependent of the associated malformations. Keywords: Congenital megalourethra, Urethroplasty